Intracranial subdural hematoma after epidural anesthesia: a case report and review of the literature - Szeto, Victor (Int J Emerg Med, 2018)
BACKGROUND: Intracranial subdural hematoma occurring as a result of a procedure that causes a puncture of the spinal dura mater is extremely rare, with less than 100 cases reported. Often, this condition is initially misdiagnosed and treated as a post dural puncture headache. CASE PRESENTATION: A woman presented to our emergency department complaining of a headache 4 days after receiving epidural anesthesia during uncomplicated childbirth. The headache’s characteristics were consistent with a post dural puncture headache, and the patient was initially treated as such. Computed tomography later revealed the presence of bilateral intracranial subdural hematomas. In light of the patient’s clinical status, treatment involved cautious observation only. Repeat imaging revealed spontaneous resolution of the hematomas, and the patient had a benign clinical course. CONCLUSIONS: Headaches are common in the postpartum period, often after receiving epidural or spinal anesthesia. While exceptionally rare, intracranial subdural hematoma may occur as a complication of any procedure that results in spinal dural puncture. The possibility of this potentially life-threatening complication must be kept in mind when evaluating these patients.